System Paradigm of Risk-Oriented Internal Control in Credit Organization - V. I. Karpunin; Ju. S. Efremova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article investigates the system of internal control in the credit organization (bank) on the basis of methodology of system-functional analysis and its description on the basis of methodology of graphic depicting of IDEF0 links. The system of internal control is shown as an internal functional sub-system of the bank meant for provision of the key function realization, which is typical of any system (and mainly, the social and economic one), i.e. the function of feedback, whose availability acts as indisputable foundation of system sustainability as it is. The authors show the functional interconnection between the service of internal control, the service of internal audit and the service of risk-management. Within the frames of system paradigm the authors identify the key functions of different types of social and economic system: the function of object systems (organization of heterogeneous elements into a united whole); the function of environmental systems (communication and coordination, developing conditions necessary to exchange between different system components); the function of process systems (harmonization of work and condition of all economic systems); the function of event (project) systems (innovational transformation of other systems). The authors put forward a hypothesis that availability (projecting) and performing these system functions determine the process of sustainable and efficient functioning of the credit organization as an organizational and economic system.